Java 9 Dependency Injection : Write loosely coupled code with Spring 5 and Guice. - Patel, Nilang (Packt Publishing, 2018)
Dependency Injection (DI) is a design pattern that allows us to remove the hard-coded dependencies and make our application loosely coupled, extendable, and maintainable. This book will be your one stop guide to write loosely coupled code using the latest features of Java 9 with frameworks such as Spring 5 and Google Guice.